Mendelian randomization analyses explore the effects of micronutrients on different kidney diseases - Shi, Chengdong; Cao, Hongliang; Zeng, Guoqiang; Wu, Hao; Wang, Yuantao (Frontiers in Nutrition, 2024)
The impact of micronutrients, including vitamins and minerals, on different kidney diseases has been reported in some observational studies; however, their causal relationship remains uncertain. We aimed to ascertain the causal genetic relationships between micronutrients and different kidney diseases using the Mendelian randomization (MR) method. Methods: Instrumental variables (IVs) for genetically predicting calcium (Ca), iron (Ir), Zinc (Zn), selenium (Se), copper (Cu), vitamin D (Vit D), and vitamin C (Vit C) levels in humans were obtained, and a bidirectional two-sample MR was used to examine potential associations between the levels of these seven micronutrients and the risk of seven different kidney diseases including hypertensive renal disease, diabetic nephropathy, IgA nephropathy, membranous nephropathy, cystic nephropathy, chronic kidney disease (CKD), and chronic tubulo-interstitial nephritis. Five different MR analyses were conducted, with the main method being the inverse variance-weighted (IVW) method. Moreover, sensitivity analyses were performed to assess heterogeneity and potential pleiotropy. The IVW method revealed that Ca levels were associated with a decreased risk of hypertensive renal disease (OR=0.61, 95% CI: 0.40-0.93, P-value=0.022), and Se levels were associated with a decreased risk of hypertensive renal disease (OR=0.72, 95% CI: 0.53-0.99, P-value=0.040), diabetic nephropathy (OR=0.83, 95% CI: 0.73-0.93, P-value=0.002), and CKD (OR=0.87, 95% CI: 0.77-0.99, P-value=0.028). Conversely, Vit D levels were associated with an increased risk of polycystic kidney disease (OR=1.76, 95% CI: 1.15-2.69, P-value=0.0095). In addition, no potential causal relationship was found between vitamin C levels, iron levels, zinc levels, and copper levels and different kidney diseases. Meanwhile, inverse Mendelian randomization showed no potential causal relationship between different chronic kidney diseases and micronutrients. The Cochrane's Q test, MR-Egger regression, and MR-PRESSO did not suggest heterogeneity and pleiotropy, providing evidence of the validity of the MR estimates. Our results indicate a cause-and-effect connection between micronutrients and certain kidney diseases, but additional study is required to provide more conclusive evidence. This research has the potential to assist clinicians in managing the consumption of specific micronutrients among individuals with chronic kidney diseases, as well as in promoting disease prevention among both healthy populations and those who are susceptible to chronic underlying conditions.